A Diagnostic Biomarker for Pediatric Generalized Anxiety Disorder Using the Error-Related Negativity - Hanna, Gregory L. (Child Psychiatry Hum Dev, 2020)
The error-related negativity (ERN) is a negative deflection in the event-related potential following a mistake that is a putative biomarker of anxiety. The study assessed the ERN as a diagnostic biomarker using receiver operating characteristic (ROC) analyses in 96 cases with anxiety disorders (AD) and 96 matched healthy controls (HC) ages 8 to 18 years. Forty-one cases had generalized anxiety disorder (GAD); 55 cases had other anxiety disorders (OAD) without GAD. ERN amplitude was significantly increased in AD cases compared to HC. The area under the curve (AUC) in the ROC analysis was .64, indicating the ERN is an inadequate diagnostic test for AD altogether. The ERN was significantly increased in cases with either GAD or OAD compared to HC. The AUC in ROC analyses with GAD and OAD was .75 and .56, respectively, suggesting the ERN provides an adequate diagnostic test for GAD but not for OAD.